The communication effectiveness among upper level and lower level management in the Ministry of Rural and Regional Development (Putrajaya) / Nor Zareela Azmira Mohd Azahari, Nor Hafiza Mokhtar and Tg Siti Erna Safiah Tg Othman - Mohd Azahari, Nor Zareela Azmira; Mokhtar, Nor Hafiza; Tg Othman, Tg Siti Erna Safiah (2009)
Communication is an exchange of feelings, ideas and information whether by speaking, writing, signal or behavior. Communication is more than merely keeping the employee updated as to what may be going on in your organization or in the company at large. People in organization typically spend over 75% of their communicating (Yousef Almulla, 2008). Effective communication is an essential component of organizational success at all levels. Numerous employee surveys have found that many problems in organization can be traced back to one primary cause poor communication. The aim of this study is to identify the main communication problems focused in the Ministry of Rural and Regional Development (Putrajaya) and to define the causes and effects of the communication problems.